Clinician's Guide to Mycosis Fungoides - Khan Mohammad Beigi, Pooya; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
Complete with dozens of color clinical photos to aid readers in diagnosis and treatment, this book includes TNM staging, description of the histopathology, and a step-by-step guide through the diagnosis of the disease. It is the most common form of cutaneous T-cell lymphoma, generally affecting the skin, though sometimes progressing internally over time. However, there is very little comprehensive information on this subject for dermatologists, dermatopathologists, and oncologists seeking deeper insight into this lymphoma in one all-inclusive text. Clinician's Guide to Mycosis Fungoidesmeets this need, covering the history, categories of disorder, molecular analysis, etiology, epidemiology, effect on body systems, disorder symptoms, and treatment. Additionally, the various recommended treatments of mycosis fungoides are explained, using clinical research and case studies as guidance.
Introduction and History -- Epidemiology -- Etiology -- Diagnosis and Management -- Staging -- Treatment -- Variants of Mycosis Fungoides -- Background -- Literature Review -- Study Goals, Hypothesis, and Design -- Treatment Plan -- Study Results -- Discussion of Study Results -- Clinical Research Case Descriptions -- Patient One -- Patient Two -- Patient Three -- Patient Four -- Patient Five -- Patient Six -- Patient Seven -- Patient Eight -- Patient Nine -- Patient Ten.
Keywords: Medicine; Dermatology; Oncology; Medicine & Public Health; Dermatology; Oncology